Reversible data hiding with selective bits difference expansion and modulus function - Aulia Arham; Hanung Adi Nugroho; Domi Sepri (Universitas Ahmad Dahlan, 2025)
The integration of the internet of things (IoT) has significantly enhanced human life but also raises concerns about information security and privacy. Information security can be achieved through cryptography, which encrypts data to make it unreadable, or steganography, which hides data within other media. For sensitive media, such as military, medical, and forensic imaging, specialized techniques like reversible data hiding (RDH) are necessary to ensure the media can be fully restored after data extraction. Many researchers have proposed improvements to the RDH method in recent years. In this study, we propose an improved RDH method utilizing difference expansion and a modulus function. The method embeds data into the 4-bit, 3-bit, and 2-bit least significant bits (LSB) of the difference value of pixels, with a range of -2 and 2. The experimental findings demonstrate that our approach achieves a embedding capacity of 0.2507 bpp with 55.445 dB of peak signal-to-noise ratio (PSNR) for common images and 0.3849 bpp with 54.6810 dB of PSNR for medical images, using 2-bit difference values. The results demonstrate that our approach surpasses previous methods and holds promise for practical applications in IoT systems and the medical field, where secure and reversible data embedding is essential.